SCIENTIFIC AND THEORETICAL FOUNDATIONS OF THE PHILOSOPHY OF SPORTS - Mamarasulov Ulugbek Umirzakovich (Galaxy International Interdisciplinary Research Journal, 2024)
The study of the essence of the sphere of physical culture and sports, its theoretical and practical problems, and socio-cultural significance "philosophy of sport", a new interdisciplinary branch of knowledge formed based on the traditions of the past, is developing all over the world by the development of time. Modern socio-philosophical views on physical culture and sport are formed by studying each specific historical period, place, and importance of sport in human life. It is known that sport was considered one of the most important types of physical education since it combined several specific features, which always created an extensive platform for heated debates not only between scientists but also between all other strata of the intelligentsia.